The Influence of Third-Party Funds, Capital Adequacy Ratio, and Non-Performing Financing on Company Profitability with Financing as an Intervening Variable in Islamic Non-banking Institution - Irman Wijaya Budi; Ganang Widodo (PT. Mawadaku Sukses Solusindo, 2024)
The researcher wrote this scientific paper so that he could set hypotheses that affect each variable to provide benefits for further writing. Through this writing, the researchers obtained the following results: 1) DPK had a positive and significant impact on financing; 2) CAR has a positive and significant impact on financing; 3) NPF has a positive impact and is quite important for financing; 4) Deposits have a positive and significant impact on Profitability; 5) CAR has a positive impact and is quite important to Profitability; 6) NPF has a positive impact and is quite important to Profitability; 7) Financing has a positive and quite important impact on Profitability; 8) DPK has a positive and quite important impact on profitability through financing mediation; 9) CAR has a positive and significant impact on Profitability through financing mediation; 10) NPF has a positive impact and is quite important to profitability mediated by financial lending.